‘… and then you shoot them!’ A Conversation with Filmmaker Jorge Thielen Armand - Steven Colburn (Janeway JS, 2018)
This paper is a transcription of a conversation between filmmakers and practice led researchers. The conversation took place at the 'Frames of Representation' global documentary cinema festival at The ICA in April 2017. CHASE was the academic partner for this festival. The conversation explores some of the challenges for documentarians and practice led researchers alike and offers a starting point for potentially fruitful conversations about methods, stakeholders, impact and other key issues.